2017
DOI: 10.1108/ijoa-12-2016-1096
|View full text |Cite
|
Sign up to set email alerts
|

Working with cancer: motivation and job satisfaction

Abstract: Purpose The purpose of this study is to investigate the motivational factors to work with cancer patients, their repercussions in job satisfaction among Portuguese healthcare professionals and to understand the role of sociodemographic and occupational variables in motivation and job satisfaction. Design/methodology/approach An instrument based on Maslow’s and Herzberg’s theories and developed by Paleologou et al. (2006) was applied to four categories of healthcare professionals. This instrument comprises fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
2
0
2
Order By: Relevance
“…In this study, job satisfaction was an extrinsic motivation outcome defined as the overall degree of contentment a healthcare professional feels based on external factors relating to their work. A study in Portugal reported that job satisfaction positively correlated with all motivation factors and was a critical element of healthcare service delivery among healthcare workers [45]. The current study found that intrinsic job satisfaction was relatively more important than job satisfaction among the participants.…”
Section: Discussionsupporting
confidence: 44%
“…In this study, job satisfaction was an extrinsic motivation outcome defined as the overall degree of contentment a healthcare professional feels based on external factors relating to their work. A study in Portugal reported that job satisfaction positively correlated with all motivation factors and was a critical element of healthcare service delivery among healthcare workers [45]. The current study found that intrinsic job satisfaction was relatively more important than job satisfaction among the participants.…”
Section: Discussionsupporting
confidence: 44%
“…Peningkatan motivasi kerja pegawai menyebabkan menyebabkan kepuasan kerja pegawai meningkat, (Diana, Ângela, Ana, & Paula, 2017;Jehanzeb et al, 2012;Nurcahyani & Adnyani 2016).…”
Section: Motivasi Kerja Dan Kepuasan Kerjaunclassified
“…Motivation, supervisor trust, support and a positive psychological contract have been this sub-cluster’s prime focus. Motivation plays a significant role in job satisfaction (Dickey et al , 2007; Dias et al , 2017). The demographic variable influences employee trust, indicating trust and workplace relationship dynamics (Chang et al , 2016).…”
Section: Thematic Cluster Analysis and Future Directionsmentioning
confidence: 99%